THE EFFECT OF FINANCIAL DEVELOPMENT ON RENEWABLE ENERGY CONSUMPTION IN CAMEROON - Nguiffo Joel Salomon; Etoa Etoa Jean Bosco (Economic Review)
The improvement of the energy structure and the development of the renewable energy sector play an important and strategic role in Cameroon's responsibilities against climate change. So, the authorities and policy makers have made great efforts to achieve this. But one of the main constraints of Cameroon's energy transition lies in financial issues, which are inevitably linked to the country's financial development. At the heart of this reflection therefore arises the question of knowing: What could be the impact of financial development on the consumption of renewable energies in Cameroon? This study therefore aims to examine the impact of financial development on the consumption of renewable energies in Cameroon over the period from 2000 to 2022. Our research is based on a Vector Autoregressive (VAR) model; seven variables of financial development have been used to explain the consumption of renewable energies in Cameroon. The results of the empirical analysis show that foreign direct investments, the evolution of bond markets and energy prices represented by the consumer price have a negative effect on the consumption of renewable energies. On the other hand, domestic credit provided by the financial sector, banking availability, economic development, and income have a positive impact on renewable energy consumption. Our empirical results provide valuable insights into the best ways to deploy capital in the renewable energy sector, in order to provide customers with cost-competitive options, and to facilitate the implementation of policies that contribute to environmental sustainability and energy security.